The Rise and Fall of Rule of Law Conditionality - Isabel Staudinger (European Papers, 2022)
(Series Information) European Papers - A Journal on Law and Integration, 2022 7(2), 721-737 | Article | (Table of Contents) I. Introduction - II. The road to rule of law conditionality - III. How the rule of law conditionality regulation became an instrument of budget conditionality - III.1. The conditionality mechanism in Regulation 2020/2092 - III.2. Article 322(1) TFEU as the correct legal basis - III.3. Sufficiently direct link - III.4. Alleged infringement of art. 7 TEU, circumvention of art. 258 TFEU, and destabilising the institutional balance - IV. Other traces of rule of law conditionality - IV.1. References to Regulation 2020/2092 - IV.2. Applying rule of law conditionality under the Recovery and Resilience Facility - V. Conclusions. | (Abstract) During the last decade, a deterioration of the respect for the EU's common values occurred. On the EU level, various procedures and instruments have been created and applied to cope with the crisis. The latest instrument, Regulation 2020/2092, was designed to establish a rule of law conditionality mechanism but has turned out as a budget conditionality mechanism. This Article examines the evolution and nature of the conditionality mechanism in said Regulation and shows why rule of law conditionality can currently rather be located in the financial instruments breathing life into the EU Green Deal than in the so-called rule of law conditionality Regulation.